Assessment of health-related quality of life in pediatric hematopoietic stem cell transplant recipients: progress, challenges and future directions. (April 2013) - Parsons, Susan K; Tighiouart, Hocine; Terrin, Norma
This article provides an overview of health-related quality of life (HRQoL) assessments in pediatric hematopoietic stem cell transplants, focusing on the relationship between child and parent proxy ratings of the child's HRQoL and how measurement of HRQoL may be incorporated into clinical decision-making. Parent and child ratings of the child's health may be affected differently by unequal access to and incongruent understanding of available information, as well as the effect of age difference on interpretation. In particular, parents and children may experience the impact of clinical events on HRQoL very differently. The recent US Federal emphasis on 'patient-centeredness' has helped fuel the development and application of more clinically functional and low-burden HRQoL measures. Future work in pediatric hematopoietic stem cell transplants must seek to capture the experiences and perceptions of all those involved.